Carpathian Ecological Network: International Legal Basis and Ukrainian Experience - Mariya Vashchyshyn (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the importance of the Framework Convention on the Protection and Sustainable Development of the Carpathians of 2003 (Carpathian Convention). Carpathian Convention created favourable conditions for the conservation of landscapes and biological diversity of mountain ecosystems of the Carpathian region. Carpathian Convention is a framework instrument, in other words, it determines the general principles concerning the solution of environmental, social and economic problems of the region. The Protocol on Conservation and Sustainable Use of Biological and Landscape Diversity to the Framework Convention on the Protection and Sustainable Development of the Carpathians has been analyzed. The advantages of international cooperation of the countries of the Carpathian region in achieving a common comprehensive result - conservation of biodiversity and improvement of social and economic level of the region and its inhabitants on the grounds of sustainable development have been defined. Carpathian Convention coordinates the economic needs with the social and environmental protection, promotes the conservation of the unique and authentic cultural and natural heritage of the Carpathian ecoregion for present and future generations. Framework Convention on the Protection and Sustainable Development of the Carpathians provides the creation of the Carpathian ecological network as a type of ecological networks at the sub-regional level, which is a part of the Pan-European ecological network. Ukraine consistently follows the bilateral and multilateral agreements, concluded with neighboring countries, concerning the protection of the environment and is involved in the creation of cross-border elements of the national ecological network. The peculiarities of the Carpathian network of protected areas have been considered. The Carpathian network of protected areas is a special form of international cooperation in environmental protection, which consists in determining by the Conference of the Parties to the Carpathian Convention the list of protected areas and in approving of regulations about them. The Conference of the Parties to the Carpathian Convention encourages the administrations of these protected areas to participate actively in international cooperation and exchange of experience in the field of the conservation of the unique biological and landscape diversity, and to reduce the negative impact on the environment of the region of the Ukrainian Carpathians. The author proves that the Carpathian Convention, except the traditional approaches concerning the protection of separate areas and species, recognizes the necessity of a broader approach to the conservation of nature. Parties to the Carpathian Convention are obliged to improve the conservation and sustainable management on the areas that are outside of protected areas, with the help of the ecosystem approach. Such an ecosystem approach to the sustainable management is applied to the spatial planning, integrated water management, agriculture, forestry, transport, infrastructure, industry, energy, tourism and cultural heritage conservation. Herewith, the interests of environmental protection shall be taken into account during the development and implementation of the economic and social policies.